RECAPITALIZATION AND ITS IMPACT ON BANK’S STABILITY, COMPETITIVENESS AND PROFITABILITY: EVIDENCE FROM INDIAN PSBs - A. Karthigeyan; V. Mariappan; R. Mani (Copernican Journal of Finance & Accounting, 2022)
There is a current argument relating to the capital infusion to the banks for strengthening capital on one side, without taking prudential measures to reduce the strains already present in the credit quality of banks on the other. The regulators thought that recapitalization of banks will be used to effectively reduce the cost of funds in the regular business provided when there is a higher lending demand. The capital infusion may turn out ineffective if there is less loan demand. On this background, this paper examines the effect of recapitalization of Indian public sector banks, and its impact on banks stability, competitiveness and profitability. Out of 21 banks, 18 banks reacted positively in case of one indicator, but failed in regard to overall indicators. Finally, the study reveals an interesting outcome that, there is no relationship between the size of the infusion and the performance of the bank. Hence, the study concludes that the capital infusion will help the banks significantly to improve the stability, competitiveness and profitability only when the banks’ fundamentals are strong, combined with the deployment of fresh funds and their managerial capability.